Probability study of airplane crash on Kartini Reactor site area - Zulfikar Erlan Bhagaskara; N N Aufanni (Jurnal Forum Nuklir, 2020)
Abstract. Probability study of airplane crash at Kartini Reactor site has been carried out. Objective of this study is to determine probability of airplane crash coming from airports around Kartini Reactor site to Kartini Reactor Site. This study was carried out in several stages, namely identification of airports around Kartini Reactor site, initial screening using SDV values (10 km for small airport and 16 km for  large airport), probability calculation of airplane crash at Kartini Reactor site and comparing the calculation result with applicable regulations. Based on the identification results there are four airports / runways around the Kartini Reactor site, they are Adi Sutjipto Airport, Adi Sumarmo Airport, Depok Runway, and Yogyakarta International Airport where distance from airport to the site between 2.26-48.23 km. After screening using SDV value, that is known only Adi Sutjipto Airport which is inside SDV radius of Kartini Reactor, so that probability of airplane crash from Adi Sutjipto Airport is calculated, i.e. 3,769x10-8 events/year is. This value is still under the provisions in BAPETEN Regulation No. 4 of 2018 i.e. maximum 10-7 events/year. So it can be concluded that Kartini Reactor is safe from the possibility of airplane crash.